Implementation of Web-Based Integrated Electronic Archives (ARTERI) at the South Labuhanbatu Regency Library and Archives Office - Syahfitri, Dini; Batubara, Abdul Karim (Inkunabula: Journal of Library Science and Islamic Information, 2025)
This study aims to analyze the implementation of the Integrated Electronic Archiving System (ARTERI) based on the web at the Library and Archives Office of Labuhanbatu Selatan Regency. This research employed a descriptive qualitative approach with data collected through interviews, observations, and documentation. The informants were four individuals: the head librarian, a librarian, a records manager, and an archivist. The results indicate that the ARTERI system has enhanced staff performance efficiency, accelerated the archiving process, and improved document accessibility for both internal and external users. However, the implementation process faced several challenges, including limited human resources with information technology skills, inadequate infrastructure, and concerns about digital archive security. To address these issues, the Library and Archives Office needs to provide technical training, gradually improve infrastructure, and implement a security system based on access controls and regular data backups. The study concludes that implementing ARTERI not only enhances the efficiency of public services but also serves as an adaptive, sustainable model for digital transformation within local government bureaucracies. It is recommended that regular system evaluations and capacity-building programs be carried out to ensure the sustainability of ARTERI implementation. Abstrak Penelitian ini bertujuan untuk menganalisis implementasi Arsip Elektronik Terintegrasi (ARTERI) berbasis web di Dinas Perpustakaan dan Kearsipan Kabupaten Labuhanbatu Selatan. Metode yang digunakan adalah pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Informan dalam penelitian ini terdiri dari empat orang, yaitu seorang kepala perpustakaan, seorang pustakawan, seorang yang berperan sebagai pengelola arsip dan arsiparis. Hasil penelitian menunjukkan bahwa sistem Arsip Elektronik Terintegrasi (ARTERI) mampu meningkatkan efektivitas kerja pegawai, mempercepat proses pengarsipan, serta mempermudah akses dokumen bagi pengguna internal dan eksternal. Meskipun demikian, proses implementasi menghadapi kendala seperti keterbatasan sumber daya manusia yang kompeten di bidang teknologi informasi, keterbatasan infrastruktur, serta isu keamanan data arsip digital. Untuk menjawab tantangan tersebut, Dinas Perpustakaan & Kearsipan perlu melakukan pelatihan teknis, peningkatan infrastruktur secara bertahap, serta menerapkan sistem keamanan berbasis kontrol akses dan pencadangan data. Kesimpulan dari penelitian ini menunjukkan bahwa implementasi Arsip Elektronik Terintegrasi (ARTERI), tidak hanya mendukung efisiensi layanan publik, tetapi juga menjadi model transformasi digital yang adaptif dan berkelanjutan di lingkungan birokrasi lokal. Penelitian ini merekomendasikan perlunya evaluasi sistem secara berkala dan penguatan kapasitas sumber daya manusia sebagai strategi keberlanjutan implementasi.